P-035 Exposure to high concentrations of non-esterified fatty acids impairs bovine sperm quality. (30th June 2022) - Idriss, A; Bulmer, D; Okello, E; Sturmey, R; Velazquez, M
Abstract: Study question: Do high concentrations of non-esterified fatty acids (NEFA) affect sperm quality? Summary answer: In vitro exposure to high NEFA concentrations induced detrimental effects on acrosome integrity, mitochondrial membrane potential, plasma membrane integrity, and DNA damage in bovine spermatozoa. What is known already: High NEFA levels present in obese individuals and in cows experiencing negative energy balance has been linked with impaired reproductive success. In vitro bovine models have showed that a high NEFA microenvironment (i.e. steric acid [SA], palmitic acid [PA], oleic acid [OA]) during oocyte maturation (Reproduction 2013, 145:33-44), fertilisation (ESHRE meeting 2021, P-176), and embryo culture (BMC Genomics 2016, 17:1004) is detrimental for blastocyst formation. However, the effect of high NEFA levels on sperm quality has been less explored. Study design, size, duration: Bovine sperm from two bulls was prepared to a maximum concentration of 20x10 6 /mL then incubated in in vitro fertilisation (IVF) medium for 4 h under different NEFA levels representing physiological (Control-1[C1], 28 μM SA, 23 μM PA, 21 μM OA) and pathophysiological (High-NEFA, 280μM SA, 230μM PA, 210μM OA), serum levels found in cows experiencing negative energy balance) concentrations. A second control (C2) group contained solvent. Participants/materials, setting, methods: Fluorescence assays (Toxicity 2018, 393:52-50) were used to evaluate simultaneously acrosome integrity (FITC-PSA), mitochondrial membrane potential (JC-1) and plasma membrane integrity (DRAQ7, Hoechst 33342). Spermatozoa (n = 800 per group, four replicates) were assessed with epifluorescence microscopy and Ziess ZEN software. Sperm DNA damage was also assessed with the Halosperm G2® kit (C1; n = 812, C2; n = 879, High-NEFA; n = 930, six replicates). Data were arcsine transformed before analysis (ANOVA, followed by LSD post hoc test). Main results and the role of chance: There was no significant difference between the control groups or between bulls in any of the variables analysed. The percentage (mean ± SEM) of spermatozoa with intact acrosome was higher in the control groups compared with high-NEFA (C1=64.50 ± 6.34%, C2=69.13 ± 4.08%, High-NEFA=49.75 ± 6.14%), but it reached statistical significance only when compared to C2 (C2 vs High-NEFA P = 0.037, C1 vs High-NEFA P = 0.096). Similarly, the percentage of spermatozoa with low mitochondrial membrane potential was increased following exposure to high concentrations of NEFA (C1=50.88 ± 5.69%, C2=45.00 ± 4.03%, High-NEFA=61.62 ± 3.38%), but a significant difference was only observed when compared to C2 (C2 vs High-NEFA P = 0.027, C1 vs High-NEFA P = 0.124). The high-NEFA group showed a higher plasma membrane damage (59.50 ± 1.06%) compared to controls (C1=47.50 ± 4.07% P = 0.01, C2=46.75 ± 1.79% P = 0.008). DNA damage was also increased in the High-NEFA group (20.00 ± 0.64%) compared to controls (C1=8.90 ± 0.71% P < 0.001, C2=6.82 ± 0.78% P < 0.001). Limitations, reasons for caution: In vitro animal models do not reflect accurately in vivo conditions and cannot be directly extrapolated to humans, but they are useful for the development of conceptual models that could eventually be tested in the target species (e.g. obese individuals). Wider implications of the findings: Our results indicate that high NEFA concentrations can impair sperm quality, and given that sperm with DNA damage can achieve fertilization (Human Reproduction 2010, 25:1594-1608), our data partially explain the decreased blastocyst formation previously observed in this model of high NEFA exposure (ESHRE meeting 2021, P-176). Trial registration number: 000